Implementasi Teori Belajar Humanistik terhadap Optimalisasi Hasil Belajar IPA di Sekolah Dasar - Santika, Dewa Gede Alit Widya; Suarni, Ni Ketut; Margunayasa, I Gede (Universitas Batanghari Jambi, 2025)
This research aims to improve the optimization of natural science (science) learning outcomes for grade 6 elementary school students through the implementation of humanist learning theory. This research uses qualitative and quantitative approaches to understand holistically. A quasi-experimental design was used with two groups of students as research subjects. The experimental group received intervention with a humanism learning model that focused on the application of humanism theory. Meanwhile, the control group followed conventional learning. Data collection involves pre-test, post-test. Data analysis includes T tests for quantitative data and thematic analysis for qualitative data. The research results show a significant increase in student learning outcomes who follow the humanism learning model, along with positive changes in students' perceptions and experiences of science learning.